Depot medroxyprogesterone acetate injection as contraceptive method - Patel, Riya R.; Sheth, Paresh N.; Mehta, Anushka S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Depot medroxyprogesterone acetate (DMPA) injection is a reversible longer acting contraceptive method. One injection every three months makes compliance better and lesser side effects makes this contraception acceptable. Methods: This is a prospective study done at our institute between July 2021 to September 2023. After prior approvals, each patient of study group had been given Inj. DMPA 150 mg intramuscularly at the time of enrolment. They were given DMPA every 3 months. All participants were followed for efficacy, side effects and continuation rates. Results: Out of 104 participants, 49.05% belonged to 18-25 years of age group, 36.53% were 2nd paras and 41.35% took injections post-delivery. In this study 51.92% patients took >=4 injections where as 45.19% discontinuation rate was found at the end of 1 year. Irregular bleeding seen in 50.96% was the most common side effect. 40.42% of total drop out was due to irregular bleeding. Efficacy of DMPA was found to be 100% in this study. Conclusions: The study concludes that DMPA is a preferable contraceptive method in all the groups of patients for spacing and to avoid unplanned pregnancy. Education and socio-economic factors play key role in acceptance and continuation of DMPA. Menstrual irregularities were found to be most common cause of discontinuation. Use of DMPA has no permanent impact on fertility and it was found to be a safe alternative method with no deleterious effect on mother’s milk secretion in lactating participants. It is reversible, non coitus dependent and long acting.